An Overview of the Tobacco Black Market in Europe - Loredana Maftei (CES Working Papers, 2012)
Cigarette smuggling is a global phenomenon and so well-organized that it poses a serious threat to public health and national economies. The aim of the article is to highlight the main definitions and classifications between illegal tobacco trade and cigarette smuggling and also to describe the general situation of Europe. Based on data retrieved from International Tobacco Trade and UNODC, the paper is focused on the price differences, source countries, supply and demand and on the analysis of reports and articles. Furthermore the main findings emphasize the role of high taxation and corruption which have affected the European economies.
Keywords: E26; O17; 330; tobacco; illegal cigarettes; smuggling; counterfeiting; underground economy Romania